Growth Mechanism of Self-Catalyzed Group III−V Nanowires - Mandl, Bernhard (American Chemical Society, 2010)
[Image: see text] Group III−V nanowires offer the exciting possibility of epitaxial growth on a wide variety of substrates, most importantly silicon. To ensure compatibility with Si technology, catalyst-free growth schemes are of particular relevance, to avoid impurities from the catalysts. While this type of growth is well-documented and some aspects are described, no detailed understanding of the nucleation and the growth mechanism has been developed. By combining a series of growth experiments using metal−organic vapor phase epitaxy, as well as detailed in situ surface imaging and spectroscopy, we gain deeper insight into nucleation and growth of self-seeded III−V nanowires. By this mechanism most work available in literature concerning this field can be described.